The usability, feasibility and fidelity of the Ethics Quarter e-learning intervention for nurse managers - Laukkanen Laura; Suhonen Riitta; Löyttyniemi Eliisa; Leino-Kilpi Helena (BMC, 2022)
Background
Nurse managers (NMs) expect support to carry out their ethical activities in a complex health care environment. In this study, the Ethics Quarter (EQ) is suggested as a new educational ethics e-learning intervention for nurse managers. The aim of this study was to evaluate the usability, feasibility and fidelity of the EQ. The goal was to create a new way to support NMs' ethical activity profile (developing one's own ethics knowledge, influencing ethical issues, conducting or implementing ethics research, identifying and solving ethical problems) for the use of healthcare organizations.
Methods
The EQ was developed under guidance of the criteria for complex interventions in health care (CReDECI2) guideline. A cross-sectional survey was conducted within the intervention group after a randomized controlled trial (the main study is registered in ClinicalTrials.gov with the identifier: 04234503). The participants were NM members of the Union of Health and Social Care Professionals in Finland (n = 95).
Results
A system usability scale (SUS) assessed the overall usability of EQ as good (a mean SUS score of 85.40 out of 100). Positive feedback about the EQ's feasibility was reported in structured and open questions (a good, necessary and practical research knowledge-based e-learning intervention for all nurse managers) and recommendations for further development (intervention contents could be even more challenging and interactive) were highlighted. Fidelity, measured with Google Analytics, reported shorter time used by NMs on the EQ education than estimated.
Conclusions
The findings support the high usability, feasibility and average fidelity of the EQ intervention and its potential while also providing evidence for the development of future ethics education. Health care organizations would benefit from adopting the EQ to support the ethical activities and ethical activity profile of NMs. Additionally, this study provides an example of ethics intervention development and evaluation in nursing research.